Функціональні особливості етикетних стереотипів привертання уваги в американському науково-академічному дискурсі - Шпенюк, І.Є. (Центр наукових досліджень та викладання іноземних мов НАН України, 2009)
The present paper considers functioning of the etiquette lexical bundles of attracting attention in scientific-academic discourse. The analysis has shown that such bundles are most frequently used with the purpose of organizing discourse, highlighting principal and secondary information, specifying, paraphrasing, providing explanation(s), illustrating, expressing authorial voice and conveying emotions.